Metadata Diversity, Interoperability and Resource Discovery Issues and Challenges - Ramesh, P.; Vivekavardhan, J.; Bharathi, K. (DESIDOC Journal of Library & Information Technology, 2015)
Information resources are available in various kinds of media and forms. To describe them there exists number of diverse metadata standards and schema. Metadata is crucial for preservation and archiving, organisation, resource discovery and information retrieval across platforms. As one metadata standard cannot be applicable for all the emerging media and document formats, a combination of them is used. In this context the present paper presents an overview on types of metadata standards and schemas, and also discusses on the issues and challenges in metadata creation, management, interoperability, and resource discovery.